Impact of Training Programs among Sericulturists of Andhra Pradesh through Technology Demonstration and Validation - S.V. Seshagiri,; P.J. Raju, (Journal of Agricultural Extension Management, 2016)
India, the largest consumer of raw silk in the world, has been mainly concentrating on production of large quantity of quality raw silk to avoid import of silk from China. Seri culture in Andhra Pradesh is a sustainable farm based economic enterprise positively favouring the rural poor in the unorganized sector because of its relatively low requirement of fixed capital and higher returns. The changes in employment and income opportunities in rural areas may be brought about by selecting a highly labour intensive and high income yielding cropping pattern and sericulture has been identified as one such sector which plays a vital role in generating gainful employment opportunities. The less skillful labour intensive activities in both cocoon production and reeling activities of sericulture compel sericulturists to hold subordinate status and hence are kept out of the interventions made for augmenting knowledge and skills and limited to lowly paid traditional activities. This scenario warrants the up-gradation of skills and knowledge of sericulturists through training on varying activities so as to enable them to harvest sustainable cocoon crop with higher income. Feedback I impact analysis carried out after the training, indicates that the training programs were quite useful and as such are to be frequently arranged for updating their knowledge and to help them gain confidence in sericulture.